2019
DOI: 10.1038/s41598-019-48635-x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion of CD4+ T-cells mediated by the Kynurenine Pathway in Melanoma

Abstract: Kynurenine pathway (KP) activation by the enzymatic activity of indoleamine 2,3-dioxygenase1 (IDO1) and kynurenine (KYN) production represents an attractive target for reducing tumour progression and improving anti-tumour immunity in multiple cancers. However, immunomodulatory properties of other KP metabolites such as 3-hydroxy kynurenine (3-HK) and kynurenic acid (KYNA) are poorly understood. The association of the kynurenine metabolic pathway with T-cell status in the tumour microenvironment were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…Activation of the KYN pathway suppresses effector T cells and induces Tregs, leading immune status to a tolerogenic state [118]. Increased KYN mediates inhibition of IL-2 signaling to reduce CD4 + T-cell survival [119]. IDO-expressing cells promote the differentiation of CD4 + T cells into Tregs expressing cytotoxic T-lymphocyte-associated protein 4, which downregulates immune responses [120].…”
Section: Immune Kynureninesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the KYN pathway suppresses effector T cells and induces Tregs, leading immune status to a tolerogenic state [118]. Increased KYN mediates inhibition of IL-2 signaling to reduce CD4 + T-cell survival [119]. IDO-expressing cells promote the differentiation of CD4 + T cells into Tregs expressing cytotoxic T-lymphocyte-associated protein 4, which downregulates immune responses [120].…”
Section: Immune Kynureninesmentioning
confidence: 99%
“…IDO-expressing cells promote the differentiation of CD4 + T cells into Tregs expressing cytotoxic T-lymphocyte-associated protein 4, which downregulates immune responses [120]. Furthermore, higher KYNA production and lower KMO expression lead to dysfunctional effector CD4 + T-cell response [119]. NAD + protects differentiated Th1, Th2, and Th17 from CD4 + T-cells, induces apoptosis of naïve CD4 + T-cells, and reduces the number of Tregs, but protects induced Tregs against apoptosis [121].…”
Section: Immune Kynureninesmentioning
confidence: 99%
“…IDO-activated cells can transform the function of APCs producing pro-inflammatory cytokine, IL-12, into anti-inflammatory cytokines including TGF-β and IL−10 [86]. IDO increases the level of KYN, which mediates the inhibition of IL-2 signaling to reduce CD4 T-cell survival [87]. Binding to AhR, KYN induces the dendritic cell and macrophage differentiation, which initially induces a highly inflammatory CD4 + T-cell subset, Th17 cells, and then further differentiate into Tregs during the resolution of inflammation [88].…”
Section: Tolerogenic Shift Of Adaptive Immune Response By Kynurenine mentioning
confidence: 99%
“…IDO-expressing cells promote the differentiation of CD4 + T cells into Treg cells expressing CTLA-4, which is a protein receptor that functions as an immune checkpoint and downregulates immune responses [90]. In addition, higher KYNA production and lower KMO expression are associated with another regulatory immune mechanism, contributing to dysfunctional effector CD4 + T-cell response [87]. NAD + induces the apoptosis of naïve CD4 + T-cells and reduces the number of Tregs, but it protects differentiated Th1, Th2, Th17, from CD4 + T-cells and induced Treg against apoptosis [91].…”
Section: Tolerogenic Shift Of Adaptive Immune Response By Kynurenine mentioning
confidence: 99%
“…It was revealed that AA was much more readily converted into 3-HANA in the brain (Maddison & Giorgini, 2015). When the immune system is activated, KMO is stimulated by cytokines in the periphery and brain, which activates inflammation-mediated dysregulation of the KP, producing neurogenic excitatory damage, which is responsible for many major brain diseases (Garrison et al, 2018), and the lower KMO expression and the higher KYNA production may contribute to dysfunctional effector CD4+ T-cell response (Rad Pour et al, 2019). In addition, KMO gets immune in neurons and astrocytes of most of the forebrain and spinal cord regions (Chiarugi, Cozzi, Ballerini, Massacesi, & Moroni, 2001).…”
Section: Nervous System Diseasesmentioning
confidence: 99%